Consumer choice of store brands across store formats: A panel data analysis under crisis periods. (March 2015) - Kaswengi, Joseph; Diallo, Mbaye Fall
Abstract: Purpose: This paper investigates the effect of marketing variables and consumer personal characteristics on store brand choice over national brands in times of crisis in France. It also seeks to clarify how store formats affect consumption strategies towards brands in turbulent times. Based on a large sample (panel of 4500 households, N =79, 789), we used a binary logit model to assess consumer choice of store brands over national brands across two different store formats (hypermarket and supermarket). Results show that, overall, marketing variables and consumer characteristics affect significantly store brand choice over national brands. However, while crisis intensity clearly moderates the relationships between marketing policy variables and store brand choice, it does not affect so extensively the relationships between consumer characteristics and store brand choice over national brands. Furthermore, hypermarket and supermarket formats are not affected similarly by crisis. This research highlights the diversity of consumer strategies developed to cope with economic crises. Theoretical and managerial implications of these findings are discussed.